2020
DOI: 10.2147/dddt.s251893
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Cordycepin Alleviates Anterior Cruciate Ligament Transection (ACLT)-Induced Knee Osteoarthritis Through Regulating TGF-β Activity and Autophagy</p>

Abstract: Introduction Osteoarthritis is the most prevalent articular disease in the elderly. We aimed to explore the role of cordycepin (COR) in the progression and development of osteoarthritis and its correlation with TGF-β activity and autophagy. Methods Sprague Dawley rats were induced by anterior cruciate ligament transection (ACLT) to establish knee osteoarthritis model. To investigate the role of COR in knee osteoarthritis, rats were injected with 5, 10, and 20 mg/kg of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Moreover, a recent study has shown that COR significantly inhibited the production of PGE 2 and NO and decreased the production of MMP13, IL-6, iNOS, and COX-2 in OA chondrocytes induced by IL-1β (Hu et al, 2014). These clues suggest that COR inhibits TGF-β activity, induces autophagy, and prevents cartilage degradation to protect the chondrocytes (Ying et al, 2014;Ashraf et al, 2019;Tao et al, 2020). It is suggested that COR may be a potential candidate drug for the prevention of OA.…”
Section: Cordycepinmentioning
confidence: 99%
“…Moreover, a recent study has shown that COR significantly inhibited the production of PGE 2 and NO and decreased the production of MMP13, IL-6, iNOS, and COX-2 in OA chondrocytes induced by IL-1β (Hu et al, 2014). These clues suggest that COR inhibits TGF-β activity, induces autophagy, and prevents cartilage degradation to protect the chondrocytes (Ying et al, 2014;Ashraf et al, 2019;Tao et al, 2020). It is suggested that COR may be a potential candidate drug for the prevention of OA.…”
Section: Cordycepinmentioning
confidence: 99%